Pengaruh Kepemimpinan Transformasional, Pengawasan Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Perum Damri - Agung Riskiansyah; Amelia Anwar (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Leadership is a central issue in agency management and largely determines the success or failure of management activities. The success of a leader with his leadership will support the formation of an effective leadership style. Decision. taken by a leader has a big influence on the continuity of activities and development of the institution. The development of an agency depends on its leader. If the agency is led well and correctly, the agency will develop rapidly, and vice versa, if the company is not led well, the company will not develop well either. So the figure of a leader is very influential in the company. As a leader, you need to pay attention to your leadership because your leadership style can be an example for other employees. A leader can have a positive or negative impact on the performance of the employees he leads. Because leadership is a force of enthusiasm and creative moral force that is able to influence members to change their attitudes so that they can work in accordance with the wishes of the leader. So a leader must be able to study the character of his employees so that he can evaluate himself and find out whether his leadership is in line with his employees' expectations.